Erythrocyte Salt Sedimentation Assay Does Not Predict Response to Renal Denervation - Vonend, Oliver; Martin, Ole; Rump, Lars C.; Kroepil, Patrick; Stegbauer, Johannes (Frontiers in Medicine, 2018)
Renal denervation (RDN) has recently been shown to be effective in patients without antihypertensive medication. However, about 30% of patients do not respond to RDN, and therefore, there exists a need to find predictors of response. Individuals are either salt-sensitive (SS) or non-salt-sensitive (NSS) in terms of their blood pressure (BP) regulation. The sympathetic nervous system can influence water and salt handling. RDN reduces sympathetic drive and has an impact on salt excretion. The present study was conducted to test the influence of salt sensitivity in terms of the BP reducing effect after RDN procedure. Salt sensitivity was estimated using the in vitro Erythrocyte Salt Sedimentation Assay (ESS). In 88 patients with resistant hypertension, RDN was performed. Office BP and lab testing were performed at baseline and at month 1, 3, 6, 12, 18, and 24 after RDN. A responder rate of 64.7% has been observed. Salt sensitivity measurements (ESS-Test) were completed in a subgroup of 37 patients with resistant hypertension. In this group, 15 were SS and 17 were salt-resistant according to the in vitro assay, respectively. The responder rate was 60% in SS patients and 59.1% in NSS patients, respectively. Electrolytes as well as aldosterone and renin levels did not differ between the two groups at baseline and in the follow-up measurements. The present study showed that salt sensitivity, estimated using the ESS in vitro test, did not affect the outcome of RDN and, therefore, does not help to identify patients suitable for RDN.